Genetic diversity analysis in radiation induced small grain mutants of rice (Oryza sativa) - ARUNACHALAM, P; VANNIARAJAN, C; SOUFRAMANIEN, J; LALITHA, R; PALANIYAPPAN, S (The Indian Journal of Agricultural Sciences, 2024)
Present study was carried out during rainy (kharif) 2018 and winter (rabi) seasons of 2018–19 at Agricultural College and Research Institute (Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu), Madurai, Tamil Nadu aimed to understand extent of genetic diversity among small grain mutants and group them by multivariate analysis to excise further selection for grain quality and grain yield improvement. The small grain mutants were grouped into 10 clusters based on genetic diversity by D2 values. The maximum cluster distance was estimated between cluster IX and cluster VIII and least inter cluster distance was obtained between cluster V and cluster X. After early generation selection of mutants for small grain size and early maturity; from remaining variability, the trait grain yield/plant contributed maximum to genetic diversity. Which offers scope for selecting high yielding genotypes with reduced grain size. The high positive values of the co- efficient of the vector were obtained from the total tillers/ plant, number of productive tillers, plant height at maturity, number of grains/panicle, and number of filled grains/ panicle from PC 1 and PC 2. Grouping based on PC 1 and PC 2 biplots helps to understand the contribution of traits to each group of genotypes. The information derived from this study will help to develop rice cultivars with improved grain quality and grain yield.